Vitrectomy for full-thickness macular hole developed during aflibercept treatment for wet age-related macular degeneration - Agnieszka Nowosielska (Klinika Oczna)
A 72-year-old male, undergoing aflibercept treatment for wet age-related macular degeneration (AMD) in his left eye, developed a full-thickness macular hole after the second injection of the medication. The additional emergence of a macular hole caused a sudden deterioration in left eye visual acuity. The patient chose to undergo macular hole surgery in the affected eye. Because of concomitant cataract in the left eye, phacoemulsification of the lens was performed, followed by vitrectomy with removal of the internal limiting membrane (ILM) and SF6 tamponade. The macular hole was successfully closed, leading to an improvement in vision, limited only by the existing macular damage from wet AMD. After the procedure, treatment of wet AMD with aflibercept in the left eye was continued. The follow-up period was four years. During this time, the patient’s visual acuity stayed consistently at a level of 0.2.